Implementasi Pendidikan Inklusi di Kelompok Bermain - Marliana, Lia; Dewi, Nurul Fitria Kumala; Jaya, Dahlan Eka (PAUDIA: Jurnal Penelitian dalam Bidang Pendidikan Anak Usia Dini, 2025)
Inclusive education is a reform in the world of education that aims to improve quality, anti-discrimination, equalize or expand access to education and efforts to change the public's view of Children with Special Needs (ABK). This study aims to describe inclusive education services in Playgroups. The study focused on three Playgroups in Jatiuwung District. The research method used was qualitative descriptive and data collection techniques using observation, interviews and documentation. In the observation activity, the researcher observed teaching and learning activities in three playgroups that implemented inclusive education, then interviews were conducted to determine the supporting factors and obstacles in implementing inclusive education. The documentation was carried out to show that the researcher had indeed conducted interviews with the principal, teachers and parents of students to obtain research results. The results of the study showed that inclusive education services in Playgroups had not been running optimally. Although efforts have been made, there are still obstacles, namely the lack of training for educators, there are no educators who are graduates of Special Education (PLB), there is no responsive curriculum for ABK and inadequate school facilities. This research is expected to provide recommendations for school principals and stakeholders, in this case the Ministry of Education, to improve the quality of inclusive education, so that all children, including children with special needs, can obtain equal access to education.